Fungal Diversity and Evaluation of Ochratoxin A Content of Coffee from Three Cameroonian Regions - N. D. Nganou; E. S. Tchinda; T. N. Noumo; H. T. Mouafo; A. T. Sokamte; L. N. Tatsadjieu (Journal of Food Quality)
The present study had the objective to assess the ochratoxin A content of coffee through chromatographic analysis and design a method using PCR-DGGE to analyze at the same moment the totality of fungal flora present in the coffee samples in order to determine their geographic origin. 96 samples of coffee were collected from the west region (Bafoussam and Dschang), centre region (Bafia), and east region (Batouri) of Cameroon during two years (2017 and 2018). Two treatments (dry and wet routes) were evaluated at three different steps of coffee processing (parchment coffee, green coffee, and husk coffee). The characterization of the fungal profile was done with PCR-DGGE and sequencing. The levels of OTA were assessed using HPLC analysis. The results indicated that the toxinogenic mycoflora associated with coffee beans was mainly Aspergillus niger, A. carbonarius, and A. ochraceus. PCR-DGGE data revealed that each sampling site is characterized by a specific fungal profile. Despite the influence of the treatment on the fungal population of coffee, bands common to samples coming from the same site were observed. These bands could therefore constitute potential biological markers to trace back to the origin of coffee. OTA was detected in most of the coffee samples analyzed and only few samples contented OTA at levels higher than the maximum tolerable limit for food intended for human consumption. The OTA content of coffee was significantly influenced by the sampling step and the sampling period.